Comparing Asian Gypsy Moth [Lymantria dispar asiatica (Lepidoptera: Erebidae) and L. dispar japonica] Trap Data From East Asian Ports With Lab Parameterized Phenology Models: New Tools and Questions. (11th February 2020) - Trotter, R Talbot; Limbu, Samita; Hoover, Kelli; Nadel, Hannah; Keena, Melody A
Abstract: Management of the European gypsy moth [ Lymantria dispar dispar (Linnaeus)] in North America has benefited from more than a century of research. The East Asian strains of the gypsy moth, however, bring new challenges including multiple subspecies ( Lymantria dispar asiatica Vnukovskij and Lymantria dispar japonica Motschulsky), broad distributions across heterogeneous habitats, and a lack of data on the variation in the phenology of source populations, which may affect risk. To address these issues, published phenology parameters for eight populations of Asian gypsy moth were used to develop eight strain-specific agent-based phenological models. These models were applied to 47 ports in East Asia where the Asian gypsy moth is native, and output was compared with available trap data to assess the role of interpopulation variation in phenological parameters in predicting moth flight among varied locations, assess variation in the performance of models among years, and assess the importance of modeling phenology using parameters from a 'local' moth population. Variation in phenological parameters among the eight populations yielded variation in predicted flight times among the 47 ports analyzed, and the use of 'local' populations did not generally improve model fit. Model accuracy varied substantially among ports and among years within some ports. The larva-to-adult agent-based models described here have utility in estimating flight periods for some ports in their current form, but variation in model quality across the landscape suggests that there is potential for unsampled and unparameterized moth populations and factors that remain to be quantified.